Evidence for Increased Chlamydia Case Finding After the Introduction of Rectal Screening Among Women Attending 2 Canadian Sexually Transmitted Infection Clinics. (21st October 2014) - Gratrix, Jennifer; Singh, Ameeta E.; Bergman, Joshua; Egan, Caroline; Plitt, Sabrina S.; McGinnis, Justin; Bell, Christopher A.; Drews, Steven J.; Read, Ron
Abstract : The prevalence of rectal Chlamydia trachomatis ranged from 11.7% to 13.5% after introducing screening in female sexually transmitted infection (STI) clinic attendees. Case-finding rates increased from 21.7% to 88.2%, those who were contacts to an STI benefiting least from screening. Abstract: Background. Chlamydia trachomatis is the most common notifiable disease in Canada, and extragenital sites are believed to serve as hidden reservoirs for ongoing transmission of infection. There are no specific Canadian screening guidelines for asymptomatic individuals from extragenital sites. We sought to determine the prevalence and factors associated with rectal C. trachomatis among female sexually transmitted infection (STI) clinic attendees in Alberta, Canada. Methods. Between 20 July and 31 December 2012, all female attendees at 2 Provincial STI clinics receiving a pelvic examination, regardless of a history of anal intercourse, were screened for rectal C. trachomatis using the Gen-Probe Aptima COMBO 2 Assay. Demographic and behavior variables were compared between rectal-only chlamydia cases and genitourinary cases using χ 2 or Fisher exact test, Mann–Whitney test, and logistic regression. Results. A total of 3055 women were screened for rectal chlamydia. The prevalence of rectal chlamydia ranged from 11.7% to 13.5%. There were 133 rectal-only cases, increasing case detection by 44.3% from 300 genitourinary cases to 433 total cases, ranging from 21.7% to 88.2% by clinic. Women who were a contact to an STI were less likely to have rectal-only chlamydia for both clinics ( P ≤ .001). Conclusions. Our findings add to the growing body of evidence supporting universal rectal screening in high-risk women such as those undergoing pelvic exams at STI clinics.